Coagulation Factor Binding Orientation and Dimerization May Influence Infectivity of Adenovirus-Coagulation Factor Complexes - Irons, Eric E. (American Society for Microbiology, 2013)
Adenoviruses (Ads) are promising vectors for therapeutic interventions in humans. When injected into the bloodstream, Ad vectors can bind several vitamin K-dependent blood coagulation factors, which contributes to virus sequestration in the liver by facilitating transduction of hepatocytes. Although both coagulation factors FVII and FX bind the hexon protein of human Ad serotype 5 (HAdv5) with a very high affinity, only FX appears to play a role in mediating Ad-hepatocyte transduction in vivo. To understand the discrepancy between efficacy of FVII binding to hexon and its apparently poor capacity for supporting virus cell entry, we analyzed the HAdv5-FVII complex by using high-resolution cryo-electron microscopy (cryo-EM) followed by molecular dynamic flexible fitting (MDFF) simulations. The results indicate that although hexon amino acids T423, E424, and T425, identified earlier as critical for FX binding, are also involved in mediating binding of FVII, the FVII GLA domain sits within the surface-exposed hexon trimer depression in a different orientation from that found for FX. Furthermore, we found that when bound to hexon, two proximal FVII molecules interact via their serine protease (SP) domains and bury potential heparan sulfate proteoglycan (HSPG) receptor binding residues within the dimer interface. In contrast, earlier cryo-EM studies of the Ad-FX interaction showed no evidence of dimer formation. Dimerization of FVII bound to Ad may be a contributing mechanistic factor for the differential infectivity of Ad-FX and Ad-FVII complexes, despite high-affinity binding of both these coagulation factors to the virus.